Pengaruh Social Media Marketing Terhadap Purchase Intention dengan Brand Image Sebagai Mediator dan Product Involvement Sebagai Moderator Pada Produk Sunscreen Facetology - Ayu Safitri; Fachmi Tamzil (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of social media marketing on purchase intention, with brand image as a mediating variable and product involvement as a moderating variable in Facetology sunscreen products. This research adopts a quantitative approach using primary data collected through questionnaires distributed to 180 respondents in the Greater Jakarta (Jabodetabek) area who met the research criteria. The data analysis technique employed is Structural Equation Modeling based on Partial Least Squares (PLS-SEM) using SmartPLS 4 software. The results indicate that social media marketing has a positive and significant effect on both brand image and purchase intention, meaning that the more effective the digital marketing strategy implemented, the stronger the brand image formed and the higher the consumers’ purchase intention. Furthermore, brand image is proven to mediate the relationship between social media marketing and purchase intention, indicating that brand image plays a crucial role in bridging the influence of digital marketing on consumer decisions. In addition, product involvement is found to strengthen the effect of brand image on purchase intention, where consumers with a higher level of product involvement tend to place greater importance on brand image in their purchasing decision-making process. These findings suggest that the effectiveness of digital marketing depends not only on promotional activities but also on the ability to build brand image and sustain consumer involvement.